Macroeconomics - Abel, Andrew B. 1952-; Bernanke, Ben; Croushore, Dean Darrell 1956- (Pearson, 2024)
What is taught in intermediate macroeconomics courses-and how it is taught-has changed substantially in recent years. Previous editions of Macroeconomics played a major role in these developments. The eleventh edition provides lively coverage of a broad spectrum of macroeconomic issues and ideas, including a variety of new and updated topics. In preparing the eleventh edition, we viewed our main objective to keep the book fresh and up-to-date, especially in light of the worldwide pandemic and the many new tools used by the Federal Reserve in response to it"--